Biosynthesis of nanoparticles using eco-friendly factories and their role in plant pathogenicity: a review. Issue 1 (January 2018) - Nayantara,; Kaur, Pawan
Abstract: Nanoparticles (NPs) have been synthesized by various methods like physical, chemical and biological methods. Physical and chemical methods are costly and toxic to the environment. So there is an emerging need for production of nanoparticles using nontoxic, eco-friendly and reliable methods to expand their applications in agriculture field. Best option to achieve this goal is the use of biological entities such as microorganisms and plant extracts to synthesize nanoparticles. The main focus of this review is to compile the studies of synthesis of nanoparticles using "eco-friendly nano-factories" i.e., plant extract and microorganisms. Agriculture is an area where new technologies are often applied to improve the yield of crops. Plant diseases are one of the major factors that affect crop productivity. The problem with disease management lies with the detection of the exact stage of prevention. The employment of nanoparticles in agriculture field with some beneficial effects to the crops will be promising step toward nano-revolution in agriculture field. This review also summarizes antimicrobial activity of nanoparticles, their influence on the plant growth parameters and their role in plant pathogenicity.